Sex and ethnic/racial differences in disordered eating behaviors and intuitive eating among college student - Yoon, Cynthia; Mai, Dan; Kinariwala, Kush; Ledoux, Tracey; Betts, Randi; Johnston, Craig (Frontiers in Psychology, 2023)
Introduction Eating behaviors encompass disordered eating behaviors (e.g., overeating, binge eating, and associated symptoms of binge eating) and intuitive eating. Certain disordered eating behaviors, including binge eating, are more prevalent among female and ethnic/racial-minority college students than male and/or non-Hispanic White college students. However, sex and ethnic/racial differences among college students with other disordered eating (e.g., associated symptoms of binge eating) and intuitive eating behaviors remain unclear. Methods In 2022, 887 college students (Mage = 20.9 ± 2.6 years) self-reported their sex, ethnicity/race, disordered eating behaviors (e.g., overeating, binge eating, associated symptoms of binge eating), and intuitive eating. To examine sex and ethnic/racial differences among these students, we used modified Poisson regressions for students who reported disordered eating and linear regressions for students who reported intuitive eating. Results Except for overeating, disordered eating behaviors were more prevalent among female [adjusted prevalence ratio (aPR) = 1.3–1.8] than male college students after adjusting for sociodemographic variables, whereas intuitive eating scores did not differ by sex. Across ethnic/racial groups, disordered eating was more prevalent among all ethnic/racial-minority college students (aPR = 1.2–2.3) than non-Hispanic White college students after adjusting for sociodemographic variables. Moreover, non-Hispanic Black or African American college students had higher intuitive eating scores than non-Hispanic White college students (adjusted β = 0.7, 95% CI = −0.2, 1.6). Conclusion In our sample, notable differences emerged in the prevalence of disordered eating behaviors and mean scores by sex and ethnicity/race, while differences in intuitive eating scores emerged based on ethnicity/race.